Case report: Identification of the tropical rat mite (Ornithonyssus bacoti) on a domestic donkey in France - Dumitrache, Mirabela Oana; Györke, Adriana; Julien, Florie; Kondratjeva, Jevgenija; Cadiergues, Marie-Christine (Frontiers in Veterinary Science, 2023)
A twenty-five-year-old donkey was referred for a generalized, pruritic and severe exfoliative dermatitis that had been evolving for several years, with deterioration in the last few months. Close examination of the skin surface revealed numerous small, dark, mobile elements identified as Ornithonyssus bacoti confirmed by DNA sequencing. The severity, type and topography of the lesions called for complementary examinations, leading to a second diagnosis of cutaneous epitheliotropic T-cell lymphoma. The lack of clinical improvement after antiparasitic therapy despite parasite clearance, suggests opportunistic behavior of Ornithonyssus bacoti. To the best of our knowledge, this is the first report of the presence of a tropical rat mite on a donkey, thus expanding the known host spectrum of this zoonotic parasite. Further potential questions concern the implication of this new host as a possible source of human contamination.